Formación de investigadores: en busca de un modelo de excelencia (2015)
This review article makes an exploration on the training of researchers, from the study of different concepts. These are the skills, training, staff development, thought processes, the process of teaching and learning and pedagogy. The document is the publication of the first phase of a project, which seeks to structure a model for training highly qualified researchers. From the information obtained in this review, we will proceed to design a poll in a second phase, with the primary purpose of obtaining information to identify the skills and thought processes. Processes to be developed, in order to achieve high productivity and intellectual investigators.